On Suitability of Day-Night Average Sound Level Descriptor in Indian Scenario - GARG, Naveen (Archives of Acoustics, 2019)
The paper analyzes the monthly day equivalent levels, Lday (06–22h) and night equivalent levels, Lnight (22–06 h) values observed in year 2015 and 2016 for the 70 locations whereby continuous noise monitoring is conducted under the National Ambient Noise Monitoring Network (NANMN). The study exclusively analyzes the ambient noise data acquired for 25 locations in commercial zone, 12 in industrial, 16 in residential and 17 in silence zones. The analysis of (Lday–Lnight) for 70 locations under observations reveals that 10 dB night time adjustment in day-night average sound level descriptor is not appropriate in such a scenario and as such it is recommended to use day-night average sound level and day-evening-night average sound level descriptors without any 10 dB night time adjustment or 5 dB evening time adjustments. The analysis and conclusions of the present study shall be very useful for developing single value noise descriptor correlating the noise annoyance and health effects in Indian perspectives.